A Non‐Proxied Empirical Investigation of Cultures Effect on Corruption. (26th July 2018) - Mornah, Dekuwmini; Macdermott, Raymond J.
ABSTRACT: We empirically examine the effect of two measures of culture, the World Values Survey and Hofstede's six dimensions, on three measures of corruption, Transparency International's CPI, the International Country Risk Guide, and the World Bank's Corruption Index. By adopting three measures of corruption and using a large data set covering many countries over many years, we offer more robust results as to the effects of aspects of culture on corruption. Using the World Values Survey, we find that Trust in society, Control over one's destiny and Respect for others decrease corruption while Obedience increases corruption. We find strong evidence that societies characterized by high Power Distance and Masculinity are more corrupt. Some evidence is found to indicate Long Term Orientation, Indulgence, and Individualism have a negative effect on corruption. The effect of Uncertainty Avoidance on corruption is unclear. The results have implications for international business leaders as well as policy makers.